Constructing Intersex: Intergeschlechtlichkeit als soziale Kategorie - Gregor, Joris Atte, (transcript, 2015)
Constructing Intersex presents the first biographical research on intersex people in the German-speaking world. Over the course of life stories, Anja Gregor proves that the local medical approach to intersexuality (though also more broadly), which tends to be shrouded in secrecy, is highly problematic. She also shows that knowing about one's own intersexuality means being able to confront pain and trauma that have been experienced, and to develop new, self-aware perspectives on body/sex/gender. In the process, intersexuality is treated as a bodily and social fact that has the potential to alter received understandings of gender.